Optimization of enzyme assisted extraction process and activity analysis of Polygonatum sibiricum polysaccharide - GULIZHADANMU Dawuti, LIU Xiaofeng, YANG Jiajun, MA Wenjin, ZHANG Kui, LI Jun, WEI Kongbin, LV Zhigang (Zhongguo niangzao)
Using Polygonatum sibiricum as raw material, P. sibiricum polysaccharide was extracted by enzyme assisted method and the extraction process was optimized by single factor and orthogonal tests. The moisture absorption and moisture retention tests were carried out with P. sibiricum polysaccharide fragments of different molecular weight obtained by dialysis, and the antioxidant capacity and structural characterization of the optimal moisturizing fragments were investigated. The results showed that the polysaccharide yield reached 24.18% under the conditions of compound enzyme addition 6%, enzymolysis time 90 min, enzymolysis temperature 50 ℃, solid and liquid ratio 1∶30 (g∶ml). When the mass concentration of the optimal moisturing fragment of P. sibiricum was more than 8 000 Da, its moisturing property was optimal. When the mass concentration of the optimal moisturing fragment of P. sibiricum polysaccharide was 6 mg/ml, the scavenging rates of DPPH, ABTS+ and hydroxyl radicals were 50.54%, 48.65% and 26.41%, respectively, which showed certain antioxidant activities. At the same time, it was found that the surface of moisturing fragment was basically smooth, with irregular flakes and intermolecular functional groups such as -OH, C-H and C=O.